Naberui Nikkana sebagai Tradisi Pembaruan Akad Nikah dalam Hukum Islam: Studi Sosiologis pada Masyarakat Kabupaten Gowa - Ananda, Nur; Chotban, Sippah; Satriani, Indra (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2026)
This study examines the Naberui Nikkana tradition that has developed in Pattapang Village, Tinggimoncong District, Gowa Regency, as a practice of renewing marriage vows carried out by married couples without going through a formal divorce process. This study aims to understand the meaning and form of this tradition, the social and cultural factors behind it, and its position in the perspective of Islamic law. This study uses a qualitative approach with a case study method. Data were obtained through in-depth interviews with ten married couples who had undergone Naberui Nikkana, as well as religious leaders and family members who were directly involved in its implementation. Data analysis was conducted descriptively and analytically through the stages of data reduction, narrative and interpretive presentation of findings, and normative testing based on Islamic legal sources and the views of scholars in fiqh munakahat.  The results of the study show that Naberui Nikkana is generally carried out after domestic conflicts, such as economic problems, family pressures, domestic violence, or doubts about the validity of the previous marriage contract. This practice factually fulfills the pillars and requirements of a valid marriage contract in Islam, including the presence of the bride and groom, guardian, witnesses, ijab kabul, and dowry agreed upon by both parties. The implementation is similar to the first marriage contract, but with an emphasis on caution and strengthening the intention to maintain the integrity of the household. From an Islamic legal perspective, the renewal of the marriage contract through this tradition can be understood as an effort to bring about benefits, particularly in maintaining family stability and preventing marital breakdown. Therefore, Naberui Nikkana can be categorized as a valid custom because it does not conflict with the provisions of Sharia law and is in line with the basic objectives of Islamic law in protecting the institution of the family.